Klick! Modulära associationsfält - Willim, Robert (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
This piece is a short examination of some occurences in an IT-company around the turn of the century 2000. The company Framfab was during some years one of the skyrocketing internet-consultancies in Sweden. In 1999 some of the employees in one of the offices started up a small project, which was to build robotsystems from Lego. This project became a part in a chain of events. There are connections between the Lego-project and the concept of one of the company’s central products, and also between Lego and how images of Framfab was formed. A central question is how associations and mindfields around the concept of modularity emerged and became materialized. This text is a short excerpt from a coming book, with the preliminary title Prefab Future which is to be published in Swedish during 2002.